A Study of the Anti-Monopoly Review Processes in the Shanghai Free Trade Pilot Zone. Issue 4 (4th July 2017) - Tang, Tang; Wang, Junjie
Abstract : Since the China (Shanghai) Pilot Free Trade Zone was founded in September 2013, in order to strength the degree of openness and the development of the Chinese economy, Guangdong Province, Tianjin, and Fujian Province established a free trade zone one after the other in April 2015. With the development and expansion of the free trade zones, there is no doubt that trade liberalization will promote the economic growth of China effectively. However, an important question that needs to be asked is how to balance the role of policy for promoting trade and maintaining fair competition among enterprises by the Anti-Monopoly Law (Ruan, 2007 ). So the way to manage the correct equilibrium between the anti-monopoly laws and policy of a free trade zone becomes an important but challenging issue. In recent years, the Chinese government has paid more attention to the process of anti-monopoly review and specific laws on anti-monopoly have been promulgated in the free trade zone. It is highly pertinent for business operators to keep abreast of the development in this area. Thus the aim of this article is to discuss the procedure and implementation of anti-monopoly review in China, analyze the anti-monopoly review in the free trade zone, and how this impacts the economic development in the China (Shanghai) Pilot Free Trade Zone (SPFTZ).